Jacek Jędruch, Constitutions, Elections and Legilatures of Poland, 1493-1993, 1998 - Dariusz Makiłła (Czasopismo Prawno-Historyczne)
Recenzja: Jacek Jędruch, Constitutions, Elections and Legilatures of Poland, 1493- 1993, New York 1998, s. 487, (= Studies presented to the International Commission for the History of Representative and Parliamentary Institutions, Vol. LXXVI).